Sympathetic Nervous Regulation in Patients with Cirrhosis: Pathogenesis of Fluid Retention and Formation of Ascites - Jens H Henriksen; Helmer Ring-Larsen; Niels Juel Christensen (Canadian Journal of Gastroenterology)
Increased circulating noradrenaline in patients with cirrhosis is due to enhanced sympathetic nervous activity and is not merely the result of decreased clearance of catecholamines. There is a direct relation between the level of arterial norndrenaline and severity of cirrhosis, increased portal pressure and fluid accumulation; patients with the hepatorenal syndrome exhibit the highest values of plasma noradrenaline. In patients with cirrhosis, the kidneys have been identified as an important source of noradrenaline ‘spillover’ into plasma, which indicates enhanced sympathetic nervous activity in these organs. Moreover, the level of plasma noradrenaline is inversely related to renal bloodflow and urinary excretion of sodium, and directly related to plasma renin, vasopressin and aldosterone. An increased spillover of noradrenaline has recently been demonstrated in the splanchnic system and superior portosystemic collaterals. Reduced central and arterial blood volume and low arterial blood pressure secondary to peripheral vasodilation are probably important afferent stimuli for enhanced sympathetic nervous activity, although a nonvolume-dependent hepatic baroreceptor may also be present. The authors conclude that the sympathetic nervous system, in concert with other regulatory systems, plays an important role in sodium-water homeostasis and fluid retention, as well as in the systemic and hepatosplanchnic circulatory derangement seen in patients with cirrhosis.